2017
DOI: 10.1016/j.drudis.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization in response to epigenetic modifiers during infection and inflammation

Abstract: Macrophages are a heterogeneous population of phagocytic cells present in all tissues. Recently, several drugs that target the epigenetic machinery have emerged as attractive molecules for treating infection and inflammation by modulating macrophages. Treatment of lipopolysaccharide (LPS)-challenged macrophages with epigenetic modifiers leads to phenotype switching. This could provide stimulatory/destructive (M1) or suppressive/protective (M2) therapeutic strategies, which are crucial in the cytokine milieu in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 99 publications
(115 reference statements)
5
115
0
5
Order By: Relevance
“…It is notable that macrophages are the first line of defense against viral infection, and it has been indicated that they are critical for the defense against influenza virus infection [21][22][23]. Moreover, macrophages undergo specific differentiation programs, depending on the local environment [18]. Nevertheless, scant literature is available about the polarization states of AMs infected with influenza virus and exposed to AFB 1 or about the roles played by AFB 1 -induced polarization in viral infection.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is notable that macrophages are the first line of defense against viral infection, and it has been indicated that they are critical for the defense against influenza virus infection [21][22][23]. Moreover, macrophages undergo specific differentiation programs, depending on the local environment [18]. Nevertheless, scant literature is available about the polarization states of AMs infected with influenza virus and exposed to AFB 1 or about the roles played by AFB 1 -induced polarization in viral infection.…”
Section: Introductionmentioning
confidence: 96%
“…The phenomenon of the existence of the two contrasting M1/M2 phenotypes is referred to as 'macrophage polarization'. Macrophage polarization can occur at any point in an inflammatory process [17]; multiple phenotypic markers, cytokines and growth factors, such as nitric oxide synthase (iNOS), TNF-α and interleukin 10 (IL-10), interact to determine the final polarization state [18]. Previous studies indicated that AFB 1 was immunotoxic to porcine alveolar macrophages (PAMs) and that AFB 1 leads to time-and dose-dependent decreases in the viability and phagocytic activity of PAMs [19]; furthermore, AFB 1 decreases proinflammatory cytokine levels and increases anti-inflammatory cytokine levels in macrophages [20].…”
Section: Introductionmentioning
confidence: 99%
“…[5] By contrast, dysregulated production of these immune mediators by macrophages during prolonged inflammation is associated with different pathological conditions, such as autoimmune diseases, and cancers. [68] In the present study, both ULPF and ULLF showed no inhibitory effect on RAW 264.7 macrophages cell proliferation in graded concentrations (10, 30, 60 µg/mL). When assessed by MTT assay, this study revealed that both lectins and polysaccharides fractions from U. lacuta were weakly active on RAW cells proliferation promoting a weak cytotoxic effects even at 60 µg/mL.…”
Section: Determination Of Tnf-α Levelsmentioning
confidence: 82%
“…No fígado, o aumento no fluxo de ácidos graxos e citocinas também favorece a resistência insulínica e a maior secreção de triglicérides nas VLDL. A dislipidemia da resistência insulínica favorece um perfil pró-aterogênico (Patel et al, 2016).…”
Section: Tecido Adiposo E Produtos De Glicação Avançadaunclassified
“…Macrófagos peritoneais representam uma população heterogênea e associam-se a perfis funcionais distintos mediados pelo estímulo do microambiente (Ghosn et al, 2010;Chawla et al, 2012;Patel et al, 2016 (Rath et al, 2014).…”
Section: Figura 16 Concentração Urinária De Substâncias Reativas Ao unclassified